Uplink Scheduling and Adjacent-Channel Coupling Loss Analysis for TD-LTE Deployment - Woon-Young Yeo; Sung Ho Moon; Jae-Hoon Kim (The Scientific World Journal)
TD-LTE, one of the two duplexing modes in LTE, operates in unpaired spectrum and has the advantages of TDD-based technologies. It is expected that TD-LTE will be more rapidly deployed in near future and most of WiMax operators will upgrade their networks to TD-LTE gradually. Before completely upgrading to TD-LTE, WiMax may coexist with TD-LTE in an adjacent frequency band. In addition, multiple TD-LTE operators may deploy their networks in adjacent bands. When more than one TDD network operates in adjacent frequency bands, severe interference may happen due to adjacent channel interference (ACI) and unsynchronized operations. In this paper, coexistence issues between TD-LTE and other systems are analyzed and coexistence requirements are provided. This paper has three research objectives. First, frame synchronization between TD-LTE and WiMax is discussed by investigating possible combinations of TD-LTE and WiMax configurations. Second, an uplink scheduling algorithm is proposed to utilize a leakage pattern of ACI in synchronized operations. Third, minimum requirements for coexistence in unsynchronized operations are analyzed by introducing a concept of adjacent-channel coupling loss. From the analysis and simulation results, we can see that coexistence of TD-LTE with other TDD systems is feasible if the two networks are synchronized. For the unsynchronized case, some special cell-site engineering techniques may be required to reduce the ACI.